Modern onkoepidemiological situation and timeliness of diagnosis of malignant neoplasms in Kiev - V. V. Kravchenko; N. M. Orlova (Journal of Education, Health and Sport, 2017)
Background The urgency of the problem of malignant neoplasms (MN) is due to the increase in morbidity and a major role in the formation of premature mortality and disability of the population. Objective: to determine the oncoepidemiological situation and to evaluate the timeliness of the diagnosis of malignant neoplasms in Kyiv in 2007-2016. Materials and methods. Analysis of epidemiology of MN and timeliness of diagnosis of oncological diseases in Kiev was carried out on the basis of materials of the statistical reporting. Results During 2007-2016 the incidence of MN in Kiev grew by 10% (from 334.2 to 367.7 per 100 thousand population). The leading localizations of MN among the men are prostate gland (13.8%), skin (except melanoma) (11.8%), trachea, bronchi, lungs (10.3%), colon (8.5%), stomach (7.5%), rectum (5.7%), bladder (5.3%). Among the women: breast (22.7%), body of the uterus, cervix and ovary (18.4%), skin (except melanoma) (10.6%), colon (7.5%), thyroid glands (5.8%). During 2007-2016 the incidence of gastric and lung cancer decreased, and the incidence of breast cancer, cervix, uterus, skin, thyroid gland, prostate, colon increased. There is a problem of untimely diagnosis of malignant neoplasms even of visual localization. In 2016 25.2% cases of oral cavity cancer, 15.5%t – breast cancer and 12.7% - rectal cancer were detected in III - IV stages of the disease. Conclusions: The main directions of increasing the timeliness of the detection of cancer diseases among the residents of the capital should be the introduction of targeted screening programs, increasing of oncological alertness among primary health care physicians, and improving of organisation and equipment of diagnostic centers.